Hardness, Corrosion Behavior, and Microstructure of Al-Cu-Mg Alloy as a Fuction of 0.3 wt.% Ti Addition and Treatment of Alloy by Polymer Solution PAG (Journal of University of Babylon for Engineering Sciences, 2023)
The effect of adding titanium (Ti) as an alloying element to Al-Cu-Mg alloy on the hardness and corrosion of this alloy was investigated. The hardness and polarization test results of samples treated for various periods by aging at 423.15 K for 5hr showed a significant increment in the Brinell hardness (HBW) improvement ratio of 113.95% (from 43HBW to 92HBW) and an extreme reduction the corrosion rate of the alloy after Ti adding decrease in the current density by 77.54% (from 58.14 µA cm-2 to 13.06 µA cm-2) with aging for 5 hr compared to the base alloy. The impact of  addition (Ti) and solution heat  treatment (in PAG)  is also reflected in the strengthening, recrystallization, and modification of the grain microstructure. These changes were clearly demonstrated by microscopic testing and proves that the addition of Ti has a considerable synergistic effect causing inhibition of recrystallization and refinement of grain size.